Development of a hardware simulator for reliable design of modular multilevel converters based on junction-temperature of IGBT modules - Jo, Seung Rae; Kim, Seok Min; Cho, Sungjoon; Lee, Kyo Beum (Electronics (Switzerland), 2019)
This paper presents the development of a hardware simulator based on the junction-temperature of insulated-gate bipolar transistor (IGBT) modules in modular multilevel converters (MMCs). The MMC consists of various power-electronics components, and the IGBT is the main factor determining the lifetime of the MMC. The failure of IGBTs is mostly due to the junction-temperature swing; thus, the thermal profile of the IGBT should be established to predict the lifetime. The thermal behavior depends on the current flowing to the IGBT, and the load-current profile is related to the application. To establish the thermal profile of the IGBT, the proposed hardware simulator generates various shapes of output currents while the junction temperature is measured. Additionally, a controller design is presented for simulation of the arm current, which includes a direct current component as well as an alternative current component with a fundamental frequency. The validity and performance of the proposed hardware simulator and its control methods are analyzed according to various experimental results.
Keywords: Arm current; Hardware simulator; IGBT module; Junction-temperature measurement; Modular multilevel converter; Reliability; Thermal profile